Long-term prognostic utility of pentraxin 3 and D-dimer as compared to high-sensitivity C-reactive protein and B-type natriuretic peptide in suspected acute coronary syndrome. (July 2016) - Mjelva, Øistein R; Pönitz, Volker; Brügger-Andersen, Trygve; Grundt, Heidi; Staines, Harry; Nilsen, Dennis WT
Background: Vascular inflammation plays a key role in the development of atherosclerosis and acute coronary syndrome (ACS), and pentraxin 3 (PTX3) is one of several novel, promising markers of inflammation. In addition, D-dimer might serve as a marker of thrombogenesis and a hypercoagulable state following plaque rupture. The present study assesses the prognostic utility of these two biomarkers as compared to high-sensitivity C-reactive protein (hsCRP) and B-type natriuretic peptide (BNP), in addition to conventional clinical risk factors for coronary heart disease in patients with suspected ACS. Methods: Chest pain patients with suspected ACS ( n  = 871) were consecutively included in a prospective, observational study with a follow-up time of 84 months. Results: At 7-year follow-up, 332 patients had died and 203 had suffered an adverse troponin T-positive, non-fatal cardiac event. In the multivariate analysis, levels of PTX3 above 5.88 ng/mL (median) and D-dimer above 436 µg/L (lower limit upper quartile) independently predicted mortality (HR 1.60 [95% CI 1.10–2.33]; p  = 0.014 and HR 1.83 [95% CI 1.20–2.78]; p  = 0.005, respectively). Also, BNP levels above 310.75 pg/mL (lower limit upper quartile) (HR 2.16 [95% CI 1.37–3.42]; p  = 0.001), but not hsCRP, independently predicted mortality. Only hsCRP and BNP also predicted future myocardial infarction (HR 1.59 [95% CI 1.05–2.40]; p  = 0.029 and HR 1.91 [95% CI 1.10–3.31]; p  = 0.021, respectively). Conclusion: High levels of PTX3, D-dimer and BNP were found to be independent, long-term predictors of all-cause mortality in chest pain patients with a suspected ACS. hsCRP and BNP also predicted future myocardial infarction.